What are the experiences of seeking, receiving and providing FGM-related healthcare? Perspectives of health professionals and women/girls who have undergone FGM: protocol for a systematic review of qualitative evidence - Evans, Catrin (BMJ Open, 2017)
INTRODUCTION: Female genital mutilation (FGM) is an issue of global concern. High levels of migration mean that healthcare systems in higher-income western countries are increasingly being challenged to respond to the care needs of affected communities. Research has identified significant challenges in the provision of, and access to, FGM-related healthcare. There is a lack of confidence and competence among health professionals in providing appropriate care, suggesting an urgent need for evidence-based service development in this area. This study will involve two systematic reviews of qualitative evidence to explore the experiences, needs, barriers and facilitators to seeking and providing FGM-related healthcare in high-income (Organisation for Economic Cooperation and Development) countries, from the perspectives of: (1) women and girls who have undergone FGM and (2) health professionals. REVIEW METHODS: Twelve databases including MEDLINE, EMBASE, PsycINFO, ASSIA, Web of Science, ERIC, CINAHL, and POPLINE will be searched with no limits on publication year. Relevant grey literature will be identified from digital sources and professional networks. Two reviewers will independently screen, select and critically appraise the studies. Study quality will be assessed using the Joanna Briggs Institute Qualitative Assessment and Review Instrument appraisal tool. Findings will be extracted into NVivo software. Synthesis will involve inductive thematic analysis, including in-depth reading, line by line coding of the findings, development of descriptive themes and re-coding to higher level analytical themes. Confidence in the review findings will be assessed using the CERQual approach. Findings will be integrated into a comprehensive set of recommendations for research, policy and practice. DISSEMINATION: The syntheses will be reported as per the Enhancing Transparency in Reporting the Synthesis of Qualitative Research (ENTREQ) statement. Two reviews will be published in peer-reviewed journals and an integrated report disseminated at stakeholder engagement events. PROSPEROREGISTRATION NUMBER: CRD42015030001: 2015 and CRD42015030004: 2015.